Penerapan Metode Rolle Playing Dalam Menıngkatkan Keterampılan Berbıcara Di Kelas I Sekolah Dasar Sukadana III - Maryani, Nani (Journal of Innovation in Primary Education, 2023)
This research was motivated by the low learning outcomes of students using the Rolle Playing method for students in class I at SD Negeri Sukadana III. This research aims to determine the improvement of speaking skills through the Rolle Playing method in Class I of Sukadana III State Elementary School, Malausma District, Majalengka Regency. The subjects in this research were class I students at SDN Sukadana III, Malausma District, Majalengka Regency, totaling 16 students. Data collection techniques use observation, interviews, tests, and documentation. The data analysis technique uses qualitative description. The results of the research show that: (1) The implementation of improving speaking skills using the Rolle Playing method in class I at SDN Sukadana III, Malausma District, Majalengka Regency has proven to be able to improve speaking skills, and (2) The use of the Rolle Playing method in improving student learning outcomes in class I at SDN Sukadana III, Malausma District, Majalengka Regency, is proven to be able to improve speaking skills, this can be seen from the increase in the class average score from student test results at each stage of the cycle, namely, the class average score in the pre-cycle was 50, in the first cycle it was 50. 53.87, and in cycle II it was 71. This research was motivated by the low learning outcomes of students using the Rolle Playing method for students in class I at SD Negeri Sukadana III. This research aims to determine the improvement of speaking skills through the Rolle Playing method in Class I of Sukadana III State Elementary School, Malausma District, Majalengka Regency. The subjects in this research were class I students at SDN Sukadana III, Malausma District, Majalengka Regency, totaling 16 students. Data collection techniques use observation, interviews, tests, and documentation. The data analysis technique uses qualitative description. The results of the research show that: (1) The implementation of improving speaking skills using the Rolle Playing method in class I at SDN Sukadana III, Malausma District, Majalengka Regency has proven to be able to improve speaking skills, and (2) The use of the Rolle Playing method in improving student learning outcomes in class I at SDN Sukadana III, Malausma District, Majalengka Regency, is proven to be able to improve speaking skills, this can be seen from the increase in the class average score from student test results at each stage of the cycle, namely, the class average score in the pre-cycle was 50, in the first cycle it was 50. 53.87, and in cycle II it was 71.